Remodelling of membrane tubules by the actin cytoskeleton. (30th April 2021) - Allard, Antoine; Lopes dos Santos, Rogério; Campillo, Clément
Abstract: Inside living cells, the remodelling of membrane tubules by actomyosin networks is crucial for processes such as intracellular trafficking or organelle reshaping. In this review, we first present various in vivo situations in which actin affects membrane tubule remodelling, then we recall some results on force production by actin dynamics and on membrane tubules physics. Finally, we show that our knowledge of the underlying mechanisms by which actomyosin dynamics affect tubule morphology has recently been moved forward. This is thanks to in vitro experiments that mimic cellular membranes and actin dynamics and allow deciphering the physics of tubule remodelling in biochemically controlled conditions, and shed new light on tubule shape regulation. Abstract : Review : Inside living cells, the remodelling of membrane tubules by actomyosin networks is crucial for processes such as intracellular trafficking or organelle reshaping. In this review, we present in vivo examples of this remodelling, recall some results on force production by actin dynamics and membrane tubules physics, and finally show how in vitro biomimetic assays allow deciphering tubule remodelling, shedding new light on tubule shape regulation.